2010
DOI: 10.1002/chem.201002637
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sulfoxides on the Stereoselective Construction of Tetrahydrofurans: Total Synthesis of (+)‐Goniothalesdiol

Abstract: Good to excellent stereoselectivities were achieved in the reductive cyclization (with Et(3)SiH/trimethylsilyl trifluoromethanesulfonate (TMSOTf)) of enantiopure hydroxy sulfinyl ketones en route to 2,5-cis-disubstituted tetrahydrofuran skeletons. Electrostatic effects of the exocyclic sulfoxide, which stabilized the reactive intermediate oxocarbenium conformations, were responsible for the observed stereocontrol. A model is proposed to explain the results. The use of this reaction and the asymmetric β-ketosul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 94 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…25,26 Further reduction of the Reformatsky adducts with DIBAL-H or DIBAL-H/Yb(OTf) 3 afforded with high diastereoselectivity the syn,syn stereotriad 30 or the syn,anti stereotriad 31, present in many natural products. 27 The removal or transformation of the chiral sulfoxide allowed us to apply this methodology to the total synthesis of biologically active molecules 28,29 (see Section 4.5).…”
Section: Synthesis Of 2-methyl-13-syn and Anti Diolsmentioning
confidence: 99%
“…25,26 Further reduction of the Reformatsky adducts with DIBAL-H or DIBAL-H/Yb(OTf) 3 afforded with high diastereoselectivity the syn,syn stereotriad 30 or the syn,anti stereotriad 31, present in many natural products. 27 The removal or transformation of the chiral sulfoxide allowed us to apply this methodology to the total synthesis of biologically active molecules 28,29 (see Section 4.5).…”
Section: Synthesis Of 2-methyl-13-syn and Anti Diolsmentioning
confidence: 99%
“…In contrast, the 2,3-trans carbohydrate furanose derivatives present some discrepancies . For example, our group recently found that the stereochemistry in the C-glycosidations using Kishi’s protocol on d -fucose derivatives can be modulated by the protecting groups.…”
Section: Introductionmentioning
confidence: 99%